52.4: New external compensation schemes for AMOLED. (24th February 2021) - Zhang, Liuqi; Chaw, Gary; Han, Baixiang; Wu, Yuanjun; Cao, Weiran
Abstract : This work presents two new external compensation schemes for AMOLED displays. With the first solution, we can obtain the changes in Vth and mobility of the driving TFT by simply detecting in two steps. And according to the second one, we can complete the compensation for the threshold voltage(Vth) and mobility(u) changes of the driving TFT in an extremely short detection time, and which makes it possible to perform external compensation in real time. Through simulation, it is found that the amount of current variation can be suppressed within 4% using this technique (when Vth is changed within ± 4V), and when the Vth and u are changed at the same time, the current variation can be suppressed within 7%(Vth changes by 1.5V and the mobility changes by 0.5 times or Vth changes by ‐1.5V and the mobility changes by 1.5 times).